Hospital policies can create barriers to good management of opioid withdrawal. (2nd December 2022) - Saul, Helen; Gursul, Deniz; Deeney, Brendan; Harris, Magdalena; Holland, Adam
The study: Harris M, Holland A, Lewer D, et al. Barriers to management of opioid withdrawal in hospitals in England: a document analysis of hospital policies on the management of substance dependence. BMC Med 2022;20:151. To read the full NIHR Alert, go to: https://evidence.nihr.ac.uk/alert/many-hospital-policies-create-barriers-to-good-management-of-opioid-withdrawal/